2017
DOI: 10.1177/2381468317715621
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision-Making Tool for Self-Management of Home Therapies for Patients With Cystic Fibrosis

Abstract: Objective: Patients with cystic fibrosis (CF) undertake time-consuming programs of home therapies. Our objective was to develop a tool to help CF patients prioritize personal goals for some of these treatments. We describe the development and results of initial evaluation of this shared decision-making tool. Methods: Multicriteria decision-making method to develop a shared decision-making tool that integrates patient’s values and perceptions of treatment impact on functionality/sense of well-being. Treatment e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In CF care, patients with more health burden may be in the midst of acute health crises that spur changes to their existing care plans. Shared decision-making is a powerful process for ensuring that these often complex plans continue to fit the resources and constraints each individual and family brings to self-management, which is undertaken primarily outside the health care context ( 18 , 19 ). A clinic coordinator or other team members could be leveraged as an additional resource for patients and families, to better facilitate SDM.…”
Section: Discussionmentioning
confidence: 99%
“…In CF care, patients with more health burden may be in the midst of acute health crises that spur changes to their existing care plans. Shared decision-making is a powerful process for ensuring that these often complex plans continue to fit the resources and constraints each individual and family brings to self-management, which is undertaken primarily outside the health care context ( 18 , 19 ). A clinic coordinator or other team members could be leveraged as an additional resource for patients and families, to better facilitate SDM.…”
Section: Discussionmentioning
confidence: 99%
“…Individual patient utilities can be used to inform shared decision making through the use of personalized decision analyses for a variety of clinical disorders. 3,4,[58][59][60] Most recently, we examined the feasibility of performing real-time utility assessments and personalized decision analyses to facilitate patient visits with their cardiologists to discuss anticoagulation options to prevent atrial fibrillation-related stroke. 59 One could envision a future in which many preference sensitive decisions are facilitated by such an approach.…”
Section: Discussionmentioning
confidence: 99%
“…They can also support decision making at the individual patient level. 3,4 The theoretical underpinnings of utility assessment derive from von Neumann-Morgenstern utility theory. 2 The resulting health utility weights range from zero to one: one representing full health and zero representing the worst outcome, generally death.…”
Section: Background and Significancementioning
confidence: 99%
“…It is a key component of person-centered healthcare and should become the standard of care [76 ▪ ]. It has been shown that involving PwCF and their families in decision-making is associated with positive perceptions about quality of care and helped them feel like they were contributing to the care [77]. Shared decision-making leads to a partnership in developing personalized care plans based on individual medical information and standards of care while incorporating the individual's and family's preferences and goals.…”
Section: Shared Decision-makingmentioning
confidence: 99%